2000
DOI: 10.1093/geronb/55.4.s208
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Activity and Social Support to the Functional Health of Older Adults

Abstract: If changes in potentially modifiable risk factors such as activity are associated with the beginning of functional decline, early intervention may be possible before disability ensues, thus reducing the risk of disability and ultimately health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
258
1
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(285 citation statements)
references
References 30 publications
17
258
1
9
Order By: Relevance
“…The ACS is a reliable and valid instrument (Edwards, Hahn, Baum, & Dromerick, 2006;Everard, Lach, Fisher, & Baum, 2000;Tse, Douglas, Lentin, & Carey, 2013). A recent review indicated that the ACS covers the most domains of the ICF Activities and Participation domains, relative to other measures, and meets the most psychometric properties (Tse et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The ACS is a reliable and valid instrument (Edwards, Hahn, Baum, & Dromerick, 2006;Everard, Lach, Fisher, & Baum, 2000;Tse, Douglas, Lentin, & Carey, 2013). A recent review indicated that the ACS covers the most domains of the ICF Activities and Participation domains, relative to other measures, and meets the most psychometric properties (Tse et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…These functions, roles and activities comprise the meaning of the term participation, which is defined by the International Classification of Functioning, Disability and Health (ICF) as the patient's involvement in life situations [4]. Engagement in social activities has been positively correlated with well-being [5]; participation in activities has been shown to contribute to the maintenance of function and quality of life in older adults [6]. Because of the association between activity engagement, quality of life, and well-being, it is essential to understand how participation in activities may or may not be affected in individuals with PD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, participation restrictions are prevalent in the visually impaired elderly. This is an important finding since participation in society can be considered as an indicator of successful aging [54] and has a positive influence on physical and mental health [55], quality of life [56] and subjective well-being [54]. Decreased participation and activity loss are associated with an increased risk of functional [57] and cognitive decline in the elderly [58,59].…”
mentioning
confidence: 99%